Computational analysis of radiative engine oil-based Prandtl–Eyring hybrid nanofluid flow with variable heat transfer using the Cattaneo–Christov heat flux model. Issue 6 (25th January 2023) - Shah, Zahir; Rooman, Muhammad; Shutaywi, Meshal
Abstract : In the present analysis, we study the energy transference through engine oil-based Prandtl–Eyring nanofluid flow through a heated stretching surface. Abstract : In the present analysis, we study the energy transference through engine oil-based Prandtl–Eyring nanofluid flow through a heated stretching surface. The nanofluid is prepared by adding copper (Cu) and titanium dioxide (TiO2 ) nanoparticles (NPs) to the base fluid engine oil. The flow mechanism and thermal transmission are observed by exposing the nanofluid flow through the heated slippery surface. The influences of permeable surface, radiative flux and heat absorption/generation are also elaborated in this study. The flow of nanofluids has been designed using a PDEs system, which are then transformed into a set of ODEs via resemblance modification. The numerical technique "shooting method" is used to solve the acquired nonlinear set of non – dimensional ODEs. The results are physically exemplified through tables and plots. It has been detected that the accumulation of nanomaterials in the engine oil, reduces the skin friction while accelerating the energy transfer rate. The velocity field significantly decelerates with the encouragement of the porosity factor, and volume fraction of NPs. However, the temperature profile significantly escalates with the encouragement of the porosity factor, and volume fraction of NPs.